2017
DOI: 10.1101/194589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress granule-inducing eukaryotic translation initiation factor 4A inhibitors block influenza A virus replication

Abstract: Eukaryotic translation initiation factor 4A (eIF4A) is a helicase that facilitates assembly of the translation preinitiation complex by unwinding structured mRNA 5’ untranslated regions. Pateamine A (PatA) and silvestrol are natural products that disrupt eIF4A function and arrest translation, thereby triggering the formation of cytoplasmic aggregates of stalled preinitiation complexes known as stress granules (SGs). Here we examined the effects of eIF4A inhibition by PatA and silvestrol on influenza A virus (I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Influenza virus infection is also negatively influenced by the triggers that induce stress granule formation [102,103]. Indeed, this virus also inhibits the formation of stress granules, and influenza virus encoded NS1 seems to play a major role in this [104].…”
Section: Manipulation Of Stress Granule Formationmentioning
confidence: 99%
“…Influenza virus infection is also negatively influenced by the triggers that induce stress granule formation [102,103]. Indeed, this virus also inhibits the formation of stress granules, and influenza virus encoded NS1 seems to play a major role in this [104].…”
Section: Manipulation Of Stress Granule Formationmentioning
confidence: 99%
“…was detected by western blotting. (Slaine et al 2017;Amorim et al 2017). Our results showed that CVB3 infection did not affect the formation of Ars-induced SGs, but that the levels of p-eIF2a in CVB3infected cells treated with Ars were significantly increased, possibly due to a mechanism associated with prolonged treatment of Ars which promotes eIF2a phosphorylation.…”
Section: Discussionmentioning
confidence: 56%
“…CoV uses capindependent cis-acting RNA internal ribosome entry site (IRES) elements with eIF4A for viral translation that can also be inhibited by silvestrol [83]. Interestingly, silvestrol exhibits a potent and modest ability to inhibit IFV-A infection in A549 cells and MDCK cells, respectively, but fails to inhibit viral infection in Vero cells [84]. The antiviral effect of silvestrol on IFV infection is reversible, where drug withdrawal results in rapid dissolution of stalled preinitiation complexes (stress granules) and resumption of viral protein synthesis.…”
Section: Eif4amentioning
confidence: 99%
“…The antiviral effect of silvestrol on IFV infection is reversible, where drug withdrawal results in rapid dissolution of stalled preinitiation complexes (stress granules) and resumption of viral protein synthesis. Inhibition of IFV-A by silvestrol is associated with cytotoxicity [84]. By contrast, pateamine A irreversibly binds to eIF4A to result in an extended blockade of IFV-A replication after drug withdrawal, and it inhibits IFV-A replication in all A549, MDCK and Vero cells with minimal cytotoxicity [84].…”
Section: Eif4amentioning
confidence: 99%
See 1 more Smart Citation